2010
DOI: 10.1097/cji.0b013e3181f5dac7
|View full text |Cite
|
Sign up to set email alerts
|

Cross-trial Analysis of Immunologic and Clinical Data Resulting From Phase I and II Trials of MVA-5T4 (TroVax) in Colorectal, Renal, and Prostate Cancer Patients

Abstract: The attenuated vaccinia virus MVA has been engineered to deliver the tumor antigen 5T4 (MVA-5T4; TroVax), a surface glycoprotein expressed by most solid tumors. MVA-5T4 has been tested in 2 phase I/II and 7 phase II clinical trials in colorectal (4 trials), renal (4 trials), and prostate (1 trial) advanced cancer patients. Data have been collated from all 9 studies and used to investigate the magnitude and kinetics of 5T4-specific antibody responses after vaccination and to identify potential associations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Immune-engagement with 5T4 was also studied. 5T4-specific antibodies were observed both in MPM patients and healthy donors, with higher levels in patients and similar to levels observed in other solid cancers [17]. In our study, the difference did not reach statistical significance, probably due to the relatively small number of samples and one high healthy responder.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Immune-engagement with 5T4 was also studied. 5T4-specific antibodies were observed both in MPM patients and healthy donors, with higher levels in patients and similar to levels observed in other solid cancers [17]. In our study, the difference did not reach statistical significance, probably due to the relatively small number of samples and one high healthy responder.…”
Section: Discussionsupporting
confidence: 60%
“…In our study, the difference did not reach statistical significance, probably due to the relatively small number of samples and one high healthy responder. Furthermore, 5T4 antibody levels (without vaccination) had no prognostic value in prostate or colorectal carcinoma [17] and its significance in MPM is also unknown.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, 5T4 has been most advanced as a target for vaccines. A vaccine consisting of modified vaccinia virus vector encoding human 5T4 (MVA-h5T4, TroVax) has been tested in phase I and II clinical trials and shown to induce cellular and antibody immune responses in patients with advanced prostate, renal and colorectal cancer [16]. However, a randomized phase III trial failed to demonstrate a significant survival advantage in 365 metastatic renal cell carcinoma patients treated with TroVax as compared to 368 placebo control patients [17].…”
Section: Introductionmentioning
confidence: 97%
“…It has been tested in 500 patients in Phase I, II and III clinical trials in advanced colorectal, renal and prostate cancer. The vaccine was well tolerated and a positive association was observed between the level of vaccine-induced antibody responses and clinical outcome (Harrop et al, 2010;DW Kim et al, 2010).…”
Section: Tumour-associated Antigens In MMmentioning
confidence: 99%